2009
DOI: 10.3987/rev-08-642
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fluorescent 2-Pyrone Derivatives Using Ketene Dithioacetals for Organic EL Devices

Abstract: -In recent years, organic electro luminescent (EL) materials have received considerable attention due to their potential application in next-generation display devices with high brightness levels, wide color ranges, and wide viewing angles. Fluorescent 2-pyrone derivatives have been synthesized using a convenient method involving ketene dithioacetals, which emit fluorescence (red, green, and blue) in both solution (dichloromethane and ethanol) and solid state. The structure-activity relationships of various 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…41,42 The Tominaga protocol, a facile method, was employed to prepare 2 H -pyran-2-one systems from ketene dithioacetals and ketones (Scheme 1). 43 Ketene dithioacetals 4 were conveniently synthesized from ethyl cyanoacetate, carbon disulphide and methyl iodide or dimethyl sulfoxide in the presence of a base. 44 Under basic conditions, 4 was further treated with aromatic ketones 5 containing α-Hs to afford 6-aryl-3-cyano-4-methylthio-2 H -pyran-2-ones 6 .…”
Section: Synthesis Of Precursor: 6-aryl-34-disubstituted 2h-pyran-2-onesmentioning
confidence: 99%
“…41,42 The Tominaga protocol, a facile method, was employed to prepare 2 H -pyran-2-one systems from ketene dithioacetals and ketones (Scheme 1). 43 Ketene dithioacetals 4 were conveniently synthesized from ethyl cyanoacetate, carbon disulphide and methyl iodide or dimethyl sulfoxide in the presence of a base. 44 Under basic conditions, 4 was further treated with aromatic ketones 5 containing α-Hs to afford 6-aryl-3-cyano-4-methylthio-2 H -pyran-2-ones 6 .…”
Section: Synthesis Of Precursor: 6-aryl-34-disubstituted 2h-pyran-2-onesmentioning
confidence: 99%
“…We have found that the enol form greatly contributes to the fluorescence intensity in both nonpolar and polar solvents. In heterocyclic compounds, the arrangement of the electron-donating or electron-withdrawing groups affects the intramolecular charge transfer (ICT) and enhances the fluorescence intensity [18,[25][26][27]. In addition, we reported that the steric hindrance of the alkyl group reduces the molecular aggregation of 2-pyridone and induced AIEE-based fluorescence [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…While most α-pyrones neither fluoresce in solution nor in the solid state specific substitution patterns have been identified for fluorophore design for this heterocyclic family. Tominaga and co-workers synthesized a series of α-pyrone derivatives with emission maxima between 400 and 675 nm in the solid state and between 486 and 542 nm in chloroform [16,2426], including fluorescence quantum yields as high as 95% in solution and 58% in the solid state [16,24]. While these fluorophores were synthesized by cyclocondensation with ketene dithioacetals and substituted acetophenones other cyano-containing derivatives became accessible by desymmetrizing cyclocondensation of 1,2-diaroylacetylenes with ethyl cyanoacetate [27], similar to related studies with dialkyl malonates [28].…”
Section: Introductionmentioning
confidence: 99%